Pengaruh Teknik Self Control terhadap Disiplin Peserta Didik - April Rahmad Jaya Laoli; Hosianna Rodearni Damanik; Justin Foera-era Lase; Famahato (Counseling Milenial (CM), 2025)
This study aims to determine the effect of the self-control technique on the discipline of eighth-grade students at UPTD SMP Negeri 1 Gunungsitoli Alo’oa. The research employed a quantitative approach with a quasi-experimental design, involving class VIII-B as the experimental group and VIII-C as the control group, with a total sample of 49 students. The findings revealed a significant difference between the experimental class, which received counseling services using the self-control technique, and the control class, which did not. The t-test result showed p = 0.000 < 0.05, indicating a significant effect after the treatment. Simple regression analysis yielded a correlation value (R) of 0.935 and a coefficient of determination (R-Square) of 0.874. This means that the self-control technique contributed 87.4% to the improvement of students’ discipline, while the remaining 12.6% was influenced by other factors outside this study.